Waltheria indica is a New Host of Phytoplasma Belongs to 16SrI-B Subgroup Associated with Virescence Symptoms in China - Yu, Shao-Shuai (Plant disease, 2021)
Waltheria indica L. is a kind of medicinal plants belonging to the family of Sterculiaceae distributed in China, which extracts with many active compounds used for treatment of rheumatism and sore pains (Hua et al., 2019). During September to November 2020, the plants showing abnormal symptoms including floral virescence, leaf chlorosis and leaflet, as shown in Fig.1, were found in Dingan county of Hainan province, China, with about 70% incidence. The disease symptoms which were suspected to be infected by the phytoplasma, a phloem-limited cell-wall-less prokaryotic pathogen could not be cultured in vitro, severely impacted Waltheria indica growth resulting in financial loss and ecological damage in the location. For identification of the causal pathogen, the total DNA of symptom or symptomless Waltheria indica samples were extracted using 0.10 g fresh plant tissues using CTAB method. PCR reactions were performed using primers R16mF2/R16mR1 (Lee et al., 1993) and AYgroelF/AYgroelR (Mitrović et al., 2011) specific for phytoplasma 16S rRNA and groEL gene fragments. The target productions of the two gene fragments of phytoplasma were detected in the DNA from four symptomatic plant samples whereas not in the DNA from the symptomless plant samples. The PCR productions were sequenced and the data were deposited in GenBank. The two gene fragments of the DNA extracted from the symptom plant samples were all identical, with the length of 1340 bp 16S rRNA (GenBank accession: MW353909) and 1312 bp groEL (MW353709) gene sequence fragments, putatively encoding 437 (groEL) amino acids sequence. The phytoplasma strain was named as Waltheria indica virescence (WiV) phytoplasma, WiV-hnda strain. A Blast search based on the 16S rRNA gene fragment of WiV-hnda phytoplasma strain revealed the highest level of sequence identities (99.85%) with that of 16SrI aster yellows group members (16SrI-B subgroup), such as Onion yellows phytoplasma strain OY-M (AP006628) from Japan (Oshima et al., 2004); Periwinkle virescence phytoplasma strain PeV-hnhk (KP662136), Chinaberry witches'-broom phytoplasma strain CWB-hnsy1 (KP662119) and CWB-hnsy2 (KP662120), all the strains from Hainan island of China (Yu et al., 2017). A Blast search based on the groEL gene sequence fragment of WiV-hnda indicated 99.92% sequence identity with that of 16SrI aster yellows group members (16SrI-B subgroup) such as Onion yellows phytoplasma strain OY-M (AP006628). Homology and phylogenetic analysis by DNAMAN 5.0 and MEGA 7.0 software indicated that the phytoplasma strains of WiV-hnda, OY-M, PeV-hnhk, CWB-hnsy1 and CWB-hnsy2 were clustered into one clade based on the 16S rRNA gene fragments. WiV-hnda, OY-M and Aster yellow witches'-broom (AYWB) (CP000061) phytoplasma strains were clustered into one clade based on the groEL gene fragments. To our knowledge, this was the first time that Waltheria indica virescence disease induced by 16SrI-B subgroup phytoplasma strain was reported in China. Genetic analysis showed that WiV-hnda was closely related to the phytoplasma strains causing Onion yellows in Japan, Periwinkle virescence and Chinaberry witches'-broom disease in China